2020
DOI: 10.36987/jes.v6i2.1493
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Pengajaran Remedial Terhadap Prestasi Belajar Siswa Kelas Vii SMP Negeri 2 Rantau Selatan Pada Materi Pelajaran Kewarganegaraan Tahun Pelajaran 2015/2016

Abstract: Abstrak. Dalam penelitian ini ada kalanya peneliti menjadikan keseluruhan objek untuk diteliti. Sehingga penulis hanya mengambil sebahagian saja dari seluruh objek yang diteliti sebagai dasar untuk menarik kesimpulan. Penelitian ini bertujuan untuk mengetahui pengaruh penerapan pengajaran remedial terhadap prestasi belajar kelas VII SMP Negeri 2 Rantau Selatan pada mata pelajaran pendidikan kewarganegaraan tahun pelajaran 2015/2016. Untuk mendapatkan jawaban pada penelitian ini penulis menggunakan metode penel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
0
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
1
0
0
2
Order By: Relevance
“…Since there were no respondents who said it was very difficult, the average respondent's response for teaching preparation statements was 81.58%, which is in the very high category. This is consistent with the findings of the investigation [43] The first technique of statistical relationship man of goa mo this method requires, with a rh > rt price of 0.511 > 0.334 so that the correlation coefficient x to y is accepted (4.031 > 2.029), then the contribution to the benefits should be Ha =, it can be concluded that "There is a positive and significant relationship between learning short VII students of SMP Negeri 2 Rantau Selatan and learning logic". Results of additional studies [44] The findings of this study suggest that teachers identify pupils by looking at their math test results in order to detect learning challenges during planning.…”
Section: Resultssupporting
confidence: 93%
“…Since there were no respondents who said it was very difficult, the average respondent's response for teaching preparation statements was 81.58%, which is in the very high category. This is consistent with the findings of the investigation [43] The first technique of statistical relationship man of goa mo this method requires, with a rh > rt price of 0.511 > 0.334 so that the correlation coefficient x to y is accepted (4.031 > 2.029), then the contribution to the benefits should be Ha =, it can be concluded that "There is a positive and significant relationship between learning short VII students of SMP Negeri 2 Rantau Selatan and learning logic". Results of additional studies [44] The findings of this study suggest that teachers identify pupils by looking at their math test results in order to detect learning challenges during planning.…”
Section: Resultssupporting
confidence: 93%
“…Berdasarkan pengertian remedial menurut beberapa para ahli yaitu Menurut Tjokrosujono (2003:920) yang dikutip dari Junita (2019) pengajaran remedial adalah kegiatan yang diberikan kepada peserta didik yang belum menguasai materi pelajaran yang diberikan atau yang belum dapat mencapai standar yang telah 444 Analisis Remedial Teaching Mata Pelajaran IPA di Sekolah Dasar -Riska Lestari, Ika Chastanti, Dahrul Aman Harahap DOI: https://doi.org/10.31004/basicedu.v6i1.1920 Jurnal Basicedu Vol 6 No 1 Tahun 2022 p-ISSN 2580-3735 e-ISSN 2580-1147 ditentukan dengan tujuan supaya peserta didik tersebut dapat menguasai materi pelajaran dengan baik (Junita & Siregar, 2019). Menurut (Raharjo, 2017) yang dikutip dari Sulistiawati (2021) Jika Pengajaran Remedial diberikan kepada guru yang mendidik maka dapat memperbaiki kemampuan guru mata pelajaran (Sulistiawati et al, 2021).…”
Section: Pendahuluanunclassified
“…Keluarga merupakan tempat dimana anak menrima pendidikan yang pertama dan paling utama. Oleh sebab itu peranan keluarga sangat lah besar bagi perkembangan pendidikan anak, khususnya dalam meningkatkan prestasi belajar siswa (Junita & Siregar, 2019).…”
Section: Faktor Eksternalunclassified